Preparation method of supported nickel-based catalyst and polyether amine prepared by using supported nickel-based catalyst

The supported nickel-based catalyst is prepared by combining mixing and impregnation methods, which solves the problems of complex catalyst preparation process, high cost and low activity in the prior art, and achieves high-activity and low cost catalyst preparation, which significantly improves the efficiency and selectivity of polyetheramine synthesis.

CN119608181AActive Publication Date: 2025-03-14ZHEJIANG HUANGMA TECH CO LTD +3

Patent Information

Application Number
CN202411617152.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-13
Publication Date
2025-03-14
Estimated Expiration
2044-11-13

AI Technical Summary

Technical Problem

The preparation process of existing polyether amine synthesis catalysts is complex, has high cost, has low utilization rate of active metals, and the pore volume and specific surface area of ​​the catalyst are lost during the calcination process, which affects its activity and selectivity.

Method used

Alumina support containing active metal components was prepared by mixing and kneading, and improved molding by pore reamer, combined with impregnation method to support metal components, a high-active and low-cost supported nickel-based catalyst was prepared.

Benefits of technology

The metal loading and activity of the catalyst is significantly improved, the polyol ether conversion rate and primary amine selectivity are enhanced, the production of by-products is reduced, and the production cost is reduced, and the process flow is simplified.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005132541540000151
    Figure BDA0005132541540000151
Patent Text Reader

Abstract

The invention belongs to the technical field of fine chemical synthesis, and discloses a preparation method of a supported nickel-based catalyst and polyether amine prepared from the supported nickel-based catalyst. The preparation method comprises the following steps: S1, taking a first active metal source, aluminum hydroxide dry glue powder, an extrusion aid, a pore-enlarging agent and silica sol as raw materials, and preparing an alumina carrier containing active metal components by adopting a kneading forming mode; and S2, preparing an impregnation liquid by adopting a second active metal source, then impregnating the alumina carrier prepared in the step S1, and roasting to prepare the supported nickel-based catalyst, the first active metal source and the second active metal source each comprise a nickel source, a platinum source, a copper source and a cobalt source. The supported nickel-based catalyst prepared by the invention has the characteristics of large pore volume, large specific surface area and uniform active component distribution; when the polyetheramine is prepared by using the polyetheramine catalyst, the polyalcohol ether conversion rate and the primary amine selectivity can be remarkably improved, and the generation of byproducts is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of fine chemical synthesis, and particularly relates to a method for preparing a supported nickel-based catalyst and preparing polyetheramine using the same. Background Art

[0002] Polyetheramine (PEA) is a class of compounds with a soft polyether skeleton and one end capped with an amino group or an amine group (generally a secondary amine group, a primary amine group or a polyamine group containing active hydrogen). As a functional chemical, it has important uses in many fields such as chemical industry and medicine. At present, the synthesis methods of polyetheramine mainly include catalytic amination method, leaving group method, hydrolysis method, aminophenoxy method, aminobutyric acid ester method, cyanoalkylation method, etc. Among them, the catalytic amination method has the advantages of high raw material utilization rate, low environmental pollution, high conversion rate and good selectivity, easy separation and purification of synthetic products, and high product purity; and this method only involves one-step reaction and simple process, and is currently the first choice for large-scale industrial continuous production by foreign chemical companies. At present, polyetheramine products, especially low molecular weight polyetheramine products, are relatively scarce, which to a certain extent restricts the widespread application of polyetheramine products.

[0003] At present, the more mature fixed-bed catalysts for hydroamination can be roughly divided into three categories, copper catalysts, precious metal catalysts, and nickel catalysts. The preparation process can be roughly divided into two preparation processes, coprecipitation type and impregnation type. Coprecipitation is also a widely used polyetheramine catalyst preparation process, which is to add a precipitant to a mixed metal salt solution to precipitate two or more cations contained in the solution together to generate a precipitate mixture or a solid solution precursor, filter, wash, and thermally decompose to obtain a composite oxide. However, the properties of the precipitate largely determine the properties of the catalyst, and various factors need to be carefully determined and strictly controlled, and the operation skills are high. In the synthesis process, more alkali is consumed, the influencing factors are complex, and an efficient washing and filtering device is required, and a large amount of wastewater is generated. At the same time, when the bulk catalyst prepared by coprecipitation meets the use requirements of mechanical strength, its surface active site density is low, and the advantages of high-content active metal components cannot be fully utilized, which reduces the utilization rate of active metals and increases the preparation cost of the catalyst.

[0004] Therefore, the polyetheramine synthesis catalyst currently used is usually obtained by the impregnation method. The specific steps are mainly to first prepare an alumina carrier, then impregnate active components such as Ni and Co onto the carrier, and finally dry and calcine it. However, after two drying and calcining (the molded carrier is also dried and calcined once when it is prepared), the pore volume and specific surface area of ​​the catalyst will suffer certain losses, making its process more complicated and the catalyst cost relatively high. As we all know, the impregnation method is based on the active component being impregnated into a porous carrier in the form of a salt solution and permeating into the inner surface. Due to the limitations of this method, the loading amount of the active component is limited, and the activity of the catalyst cannot be improved. Industrial catalyst development should save time and energy consumption while considering the cost. Among them, coupling the loading and molding process to prepare a molded catalyst will be a good solution to this problem. The traditional dry mixing method for preparing a catalyst is to mix, knead, mold, dry and calcine the active component, the carrier precursor, and the binder. Catalysts prepared by the industrial dry mixing method generally have problems such as uneven dispersion of active components and poor catalyst strength. Therefore, research on new catalyst preparation technologies is of great significance for reducing catalyst production costs and improving catalyst activity. Summary of the invention

[0005] The present invention aims to solve at least one of the technical problems existing in the above-mentioned prior art. To this end, the present invention provides a method for preparing a supported nickel-based catalyst and using the supported nickel-based catalyst to prepare polyetheramine. The supported nickel-based catalyst prepared by the present invention has high activity and low cost; using the supported nickel-based catalyst to prepare polyetheramine can significantly improve the conversion rate of polyol ether and the selectivity of primary amine, and reduce the generation of by-products.

[0006] The invention provides a method for preparing a supported nickel-based catalyst.

[0007] Specifically, a method for preparing a supported nickel-based catalyst comprises the following steps:

[0008] S1, using the first active metal source, aluminum hydroxide dry rubber powder, extrusion aid, pore expanding agent and silica sol as raw materials, and preparing an alumina carrier containing active metal components by kneading and molding;

[0009] S2, using a second active metal source to prepare an impregnation solution, then impregnating the alumina support prepared in step (1), and then calcining to obtain a supported nickel-based catalyst;

[0010] In step S1 and step S2, the first active metal source and the second active metal source both include a nickel source, a platinum source, a copper source and a cobalt source. The first active metal source and the second active metal source include but are not limited to nitrates, sulfates, organic salts, chlorides, etc. of the above metals, preferably nitrates of the above metals.

[0011] Preferably, in the first active metal source, the molar ratio of nickel, platinum, copper and cobalt in the nickel source, the platinum source, the copper source and the cobalt source is 1: (0.0008-0.002): (0.06-0.08): (0.05-0.2).

[0012] Preferably, in the second active metal source, the molar ratio of nickel, platinum, copper and cobalt in the nickel source, the platinum source, the copper source and the cobalt source is 1: (0.0008-0.002): (0.06-0.08): (0.05-0.2).

[0013] In step S1 and step S2, the first active metal source and the second active metal source independently include at least one of a zirconium source, a lanthanum source, and a rhenium source.

[0014] The preparation process of step S1 includes any one of the following two methods:

[0015] (1) dissolving a first active metal source in water to prepare a kneading solution; adding an extrusion aid, a pore-enlarging agent and a silica sol to aluminum hydroxide dry rubber powder, mixing them evenly, adding the kneading solution to knead, and then molding, drying and calcining to prepare an alumina carrier containing active metal components;

[0016] (2) dissolving the first active metal source in water, adding silica sol, and preparing a kneading solution; taking aluminum hydroxide dry rubber powder, adding an extrusion aid and a pore expander, mixing evenly, adding the kneading solution to knead, and then forming, drying, and calcining to prepare an alumina carrier containing active metal components.

[0017] In the kneading process, there are two ways to add the silica sol: one is to first add the silica sol to the aluminum hydroxide dry rubber powder mixed with the extrusion aid and the pore expander, mix them evenly, and then add the kneading solution therein; the second method is to first mix and dissolve the silica sol with the first active metal source, and then add it to the aluminum hydroxide dry rubber powder mixed with the extrusion aid and the pore expander. From the effect point of view, the carrier prepared by the first method has a better pore structure.

[0018] Preferably, the silica sol includes alkaline silica sol or acidic silica sol.

[0019] Preferably, the extrusion aid includes at least one of sesbania powder, starch, cellulose and carbon powder.

[0020] Preferably, the amount of the extrusion aid added is 1%-30% of the mass of the aluminum hydroxide dry rubber powder; further preferably, the amount of the extrusion aid added is 3%-15%, 5%, 6%, 8%, 10%, 12%, etc., of the mass of the aluminum hydroxide dry rubber powder.

[0021] Preferably, the pore expanding agent is carbon black. In the molding process, using carbon black as a pore expanding agent is beneficial to the pore expansion of the carrier and the improvement of the pore distribution concentration.

[0022] Preferably, the amount of the pore expanding agent added is 1%-30% of the mass of the aluminum hydroxide dry rubber powder; further preferably, the amount of the pore expanding agent added is 3%-15%, 5%, 6%, 8%, 10%, 12%, etc., of the mass of the aluminum hydroxide dry rubber powder.

[0023] In the method (1) or the method (2), a peptizing agent is added during the preparation of the kneading solution. The peptizing agent is selected from at least one of an inorganic acid, an organic acid, and a strongly acidic anionic aluminum salt. For example, nitric acid, hydrochloric acid, oxalic acid, formic acid, acetic acid, citric acid, aluminum nitrate, etc., or a combination of several peptizing agents. The addition of the peptizing agent is beneficial to the kneading and molding of the carrier.

[0024] In method (1) or method (2), the drying process is: drying at 100-130° C. for 2-12 hours, and then calcining at 400-500° C. for 2-8 hours.

[0025] In method (1) or method (2), the calcination process is: calcination at 400-500° C. for 2-8 hours.

[0026] In the method (1) or (2), the forming process is: the kneaded material is extruded into strips on an extruder. The shape of the carrier can be adjusted by replacing the orifice plate of the extruder, and the shape can be cylindrical or irregular (such as a three-leaf clover, a four-leaf clover, or a five-tooth ball).

[0027] Preferably, in step S2, the impregnation process is: placing the alumina carrier in the impregnation solution, and impregnating it for 20-60 minutes at 35-45° C. and in a rotating state.

[0028] Preferably, in step S2, the number of impregnations is 1-5 times; more preferably, in step S2, the number of impregnations is 2-3 times. When the number of impregnations is greater than 1, the process is as follows: the alumina carrier is impregnated once and calcined once, the calcined catalyst carrier is used as a carrier again, and is impregnated with the impregnation solution and calcined again until the number of impregnations is reached.

[0029] Preferably, in step S2, the calcination process is: calcination at 400-500°C for 3-8 hours.

[0030] Preferably, the inert gas is selected from one of nitrogen, helium, neon, argon or krypton. When a mixed atmosphere of inert gas and hydrogen is selected, the volume percentage of the inert gas is 5% to 95%.

[0031] Preferably, in step S2, after the calcination process, reduction treatment and passivation treatment are also included. The reduction treatment process is: reduction at 300°C to 550°C for 40h to 70h in pure hydrogen or a mixed atmosphere of inert gas and hydrogen. The passivation treatment process is to use an oxidizing gas for surface passivation for 6h to 18h, and the oxidizing gas includes one or more of oxygen, water vapor, carbon dioxide, and air.

[0032] The invention also provides a method for preparing the polyetheramine.

[0033] Specifically, a method for preparing polyetheramine comprises synthesizing polyetheramine using a supported nickel-based catalyst prepared by the above-mentioned preparation method.

[0034] The traditional impregnation method for preparing catalysts uses a metal salt solution to impregnate the calcined carrier. After calcination, the pores of the carrier collapse, the specific surface area decreases, and the pore volume decreases. In addition, the active components on the surface and in the pores of the carrier after impregnation are decomposed into oxides after drying and calcination. Part of the pores of the carrier are blocked by the active components, resulting in a loss of internal surface area and uneven dispersion of the active components.

[0035] The present invention firstly uses a kneading method to add active metal salts to raw materials, and then forms, dries and roasts them once to obtain a carrier. During the roasting process of the carrier, the decomposition and dispersion of the active metal salts are carried out simultaneously with the decomposition of the raw materials. The active metals are retained in the pores of the carrier, which supports the catalyst structure. The molding is improved by a carbon black pore expander, and a part of the metal components are loaded by kneading, and the other part of the metal components are loaded by a coupling impregnation method, which ensures the pore structure of the catalyst while also increasing the metal loading amount.

[0036] Compared with the prior art, the present invention has the following beneficial effects:

[0037] (1) The supported nickel-based catalyst provided by the present invention increases the metal loading of the catalyst by adding a certain amount of active metal components in a kneading manner during the molding process of the alumina carrier; at the same time, the pore structure of the catalyst is maintained at a relatively stable stage by modifying the pore-enlarging agent, and finally, the activity of the catalyst can be significantly improved after the carrier containing the active metal components is impregnated with a metal solution.

[0038] (2) The present invention adopts a novel kneading method to prepare a carrier containing active metals, and then uses a comprehensive impregnation method to increase the active metal loading. The catalyst prepared by this method has the characteristics of large pore volume and specific surface area, and uniform distribution of active components; using it to prepare polyetheramines can significantly improve the polyol ether conversion rate and primary amine selectivity, and reduce the generation of by-products.

[0039] (3) Compared with the co-precipitation method, the preparation method provided by the present invention has low production cost, simple process, and is easier to realize industrialization. DETAILED DESCRIPTION

[0040] In order to make the technical scheme of the present invention more clearly understood by those skilled in the art, the following embodiments are listed for illustration. It should be pointed out that the following embodiments do not limit the protection scope of the present invention.

[0041] Unless otherwise specified, the raw materials, reagents or devices used in the following examples and comparative examples can be obtained from conventional commercial sources or by existing known methods.

[0042] Example 1

[0043] A method for preparing a supported nickel-based catalyst comprises the following steps:

[0044] (1) Preparation of kneading solution: Weigh 60 g of nickel nitrate hexahydrate, 6.5 g of cobalt nitrate hexahydrate, 3.9 g of copper nitrate pentahydrate, 0.1 g of chloroplatinic acid (39% Pt), and 5 g of nitric acid, dissolve in 90 g of deionized water, and stir to prepare a kneading solution.

[0045] (2) Mixing and kneading: Weigh 80g of aluminum hydroxide dry rubber powder, add 5g of hydroxymethyl cellulose and 5g of carbon black and mix them evenly, first add an aqueous solution of silica sol (7.7mL of silica sol is dissolved in 15mL of water, wherein the silica sol is 30% alkaline silica sol and the silica particle size is 10-30nm), mix and knead evenly to make it into a fine powder, and obtain a mixed fine powder. Then add the mixed solution to the mixed fine powder, mix and knead again until it is mixed into a uniform paste-like plastic, extrude it into 3mm strips on an extruder, and dry it in a drying oven at 110°C for 3 hours, and then calcine it in a high-temperature furnace at 550°C for 4 hours to obtain an alumina carrier containing active metal components.

[0046] (3) Preparation of impregnation solution: Weigh 60 g of nickel nitrate hexahydrate, 6.5 g of cobalt nitrate hexahydrate, 3.9 g of copper nitrate pentahydrate, and 0.1 g of chloroplatinic acid (39% Pt), and dissolve them in 30 g of deionized water.

[0047] (4) Equal volume impregnation: 82 g of the alumina carrier containing active metal components prepared in step (2) is impregnated into the impregnation solution prepared in step (3), and the impregnation is carried out in a rotary evaporator in a 40°C water bath for 30 min. After adsorption equilibrium is reached, the temperature is raised to 90°C, the carrier is vacuum-dehydrated and dried, and then calcined at 400°C for 4 h. The calcined catalyst carrier is then used as a carrier again, and the impregnation solution is prepared again in the same proportion for a second impregnation, adsorption and calcination. Finally, the calcined oxidized catalyst is placed in a reduction furnace at a hydrogen space velocity of 400 h / min. -1The reduction was carried out at 420°C for 60 hours. After the reduction was completed, water vapor was introduced to passivate the catalyst surface for 10 hours to obtain a nickel-based supported catalyst.

[0048] Example 2

[0049] A method for preparing a supported nickel-based catalyst comprises the following steps:

[0050] (1) Preparation of kneading solution: 60 g of nickel nitrate hexahydrate, 6.5 g of cobalt nitrate hexahydrate, 3.9 g of copper nitrate pentahydrate, 0.1 g of chloroplatinic acid (39% Pt), and 5 g of nitric acid were weighed and dissolved in 90 g of deionized water, and 7.7 mL of silica sol (30% alkaline silica sol, silica particle size 10-30 nm) was added dropwise and stirred to mix.

[0051] (2) Mixing and kneading: Weigh 80 g of aluminum hydroxide dry rubber powder, add 5 g of hydroxymethyl cellulose and 5 g of carbon black, add the above-prepared solution to the aluminum hydroxide dry rubber powder containing hydroxymethyl cellulose and carbon black, mix and knead into a uniform paste-like plastic, extrude into 3 mm strips on an extruder, and dry in a drying oven at 110°C for 3 hours, and then calcine in a high-temperature furnace at 550°C for 4 hours to obtain an alumina carrier containing active metal components.

[0052] (3) Preparation of impregnation solution: Weigh 60 g of nickel nitrate hexahydrate, 6.5 g of cobalt nitrate hexahydrate, 3.9 g of copper nitrate pentahydrate, and 0.1 g of chloroplatinic acid (39% Pt), and dissolve them in 30 g of deionized water.

[0053] (4) Equal volume impregnation: 82g of the alumina carrier containing active metal components prepared in step (2) is impregnated into the impregnation solution prepared in step (3), and then impregnated in a rotary evaporator in a 40°C water bath for 30min. After adsorption equilibrium is reached, the temperature is raised to 90°C, vacuumed, dehydrated and dried, and then calcined at 400°C for 4h. Then, the calcined catalyst carrier is used as a carrier again, and the impregnation solution is prepared again in the same proportion, and the second impregnation, adsorption and calcination are performed. Finally, the calcined oxidized catalyst is reduced in a reduction furnace at 420°C for 60h at a hydrogen space velocity of 400h-1. After the reduction is completed, water vapor is introduced to passivate the catalyst surface for 10h to obtain a nickel-based supported catalyst.

[0054] Example 3

[0055] A method for preparing a supported nickel-based catalyst comprises the following steps:

[0056] (1) Preparation of kneading solution: Weigh 30 g of nickel nitrate hexahydrate, 3.25 g of cobalt nitrate hexahydrate, 1.95 g of copper nitrate pentahydrate, 0.05 g of chloroplatinic acid (39% Pt), and 2.5 g of nitric acid, dissolve in 45 g of deionized water, and stir to prepare a kneading solution.

[0057] (2) Mixing and kneading: Weigh 80g of aluminum hydroxide dry rubber powder, add 5g of hydroxymethyl cellulose and 5g of carbon black and mix them evenly, first add an aqueous solution of silica sol (7.7mL of silica sol is dissolved in 15mL of water, wherein the silica sol is 30% alkaline silica sol and the silica particle size is 10-30nm), mix and knead evenly to make it into a fine powder, and obtain a mixed fine powder. Then add the mixed solution to the mixed fine powder, mix and knead again until it is mixed into a uniform paste-like plastic, extrude it into 3mm strips on an extruder, and dry it in a drying oven at 110°C for 3 hours, and then calcine it in a high-temperature furnace at 550°C for 4 hours to obtain an alumina carrier containing active metal components.

[0058] (3) Preparation of impregnation solution: Weigh 60 g of nickel nitrate hexahydrate, 6.5 g of cobalt nitrate hexahydrate, 3.9 g of copper nitrate pentahydrate, and 0.1 g of chloroplatinic acid (39% Pt), and dissolve them in 30 g of deionized water.

[0059] (4) Equal volume impregnation: 82 g of the alumina carrier containing active metal components prepared in step (2) is impregnated into the impregnation solution prepared in step (3), and the impregnation is carried out in a rotary evaporator in a 40°C water bath for 30 min. After adsorption equilibrium is reached, the temperature is raised to 90°C, the carrier is vacuum-dehydrated and dried, and then calcined at 400°C for 4 h. The calcined catalyst carrier is then used as a carrier again, and the impregnation solution is prepared again in the same proportion for a second impregnation, adsorption and calcination. Finally, the calcined oxidized catalyst is placed in a reduction furnace at a hydrogen space velocity of 400 h / min. -1 The reduction was carried out at 420°C for 60 hours. After the reduction was completed, water vapor was introduced to passivate the catalyst surface for 10 hours to obtain a nickel-based supported catalyst.

[0060] Example 4

[0061] A method for preparing a supported nickel-based catalyst comprises the following steps:

[0062] (1) Preparation of kneading solution: Weigh 60 g of nickel nitrate hexahydrate, 6.5 g of cobalt nitrate hexahydrate, 3.9 g of copper nitrate pentahydrate, 0.1 g of chloroplatinic acid (39% Pt), and 5 g of nitric acid, dissolve in 90 g of deionized water, and stir to prepare a kneading solution.

[0063] (2) Mixing and kneading: Weigh 80g of aluminum hydroxide dry rubber powder, add 5g of hydroxymethyl cellulose and 5g of carbon black and mix them evenly, first add an aqueous solution of silica sol (7.7mL of silica sol is dissolved in 15mL of water, wherein the silica sol is 30% alkaline silica sol and the silica particle size is 10-30nm), mix and knead evenly to make it into a fine powder, and obtain a mixed fine powder. Then add the mixed solution to the mixed fine powder, mix and knead again until it is mixed into a uniform paste-like plastic, extrude it into 3mm strips on an extruder, and dry it in a drying oven at 110°C for 3 hours, and then calcine it in a high-temperature furnace at 550°C for 4 hours to obtain an alumina carrier containing active metal components.

[0064] (3) Preparation of impregnation solution: Weigh 30 g of nickel nitrate hexahydrate, 3.25 g of cobalt nitrate hexahydrate, 1.95 g of copper nitrate pentahydrate, and 0.05 g of chloroplatinic acid (39% Pt), and dissolve them in 15 g of deionized water.

[0065] (4) Equal volume impregnation: 82 g of the alumina carrier containing active metal components prepared in step (2) is impregnated into the impregnation solution prepared in step (3), and the impregnation is carried out in a rotary evaporator in a 40°C water bath for 30 min. After adsorption equilibrium is reached, the temperature is raised to 90°C, the carrier is vacuum-dehydrated and dried, and then calcined at 400°C for 4 h. The calcined catalyst carrier is then used as a carrier again, and the impregnation solution is prepared again in the same proportion for a second impregnation, adsorption and calcination. Finally, the calcined oxidized catalyst is placed in a reduction furnace at a hydrogen space velocity of 400 h / min. -1 The reduction was carried out at 420°C for 60 hours. After the reduction was completed, water vapor was introduced to passivate the catalyst surface for 10 hours to obtain a nickel-based supported catalyst.

[0066] Comparative Example 1

[0067] A method for preparing an alumina carrier containing an active metal component comprises the following steps:

[0068] (1) Preparation of kneading solution: 60 g of nickel nitrate hexahydrate, 6.5 g of cobalt nitrate hexahydrate, 3.9 g of copper nitrate pentahydrate, 0.1 g of chloroplatinic acid (39% Pt) and 5 g of nitric acid were weighed and dissolved in 90 g of deionized water.

[0069] (2) Mixing and kneading: Weigh 80 g of aluminum hydroxide dry glue powder, add 5 g of hydroxymethyl cellulose thereto, add the kneaded solution into the aluminum hydroxide dry glue powder containing hydroxymethyl cellulose, mix into a uniform paste-like plastic, extrude into 3 mm strips on an extruder, dry in a drying oven at 110°C for 3 hours, and then calcine in a high-temperature furnace at 550°C for 4 hours to obtain an alumina carrier containing active metal components.

[0070] Comparative Example 2

[0071] A method for preparing an alumina carrier containing an active metal component comprises the following steps:

[0072] (1) Preparation of kneading solution: Weigh 60 g of nickel nitrate hexahydrate, 6.5 g of cobalt nitrate hexahydrate, 3.9 g of copper nitrate pentahydrate, 0.1 g of chloroplatinic acid (39% Pt), and 5 g of nitric acid, dissolve in 90 g of deionized water, and stir to prepare a kneading solution.

[0073] (2) Mixing and kneading: Weigh 80g of aluminum hydroxide dry rubber powder, add 5g of hydroxymethyl cellulose and 5g of carbon black and mix them evenly, first add an aqueous solution of silica sol (7.7mL of silica sol is dissolved in 15mL of water, wherein the silica sol is 30% alkaline silica sol and the silica particle size is 10-30nm), mix and knead evenly to make it into a fine powder, and obtain a mixed fine powder. Then add the mixed solution to the mixed fine powder, mix and knead again until it is mixed into a uniform paste-like plastic, extrude it into 3mm strips on an extruder, and dry it in a drying oven at 110°C for 3 hours, and then calcine it in a high-temperature furnace at 550°C for 4 hours to obtain an alumina carrier containing active metal components.

[0074] Comparative Example 3

[0075] A method for preparing an alumina carrier containing an active metal component comprises the following steps:

[0076] (1) Preparation of kneading solution: 60 g of nickel nitrate hexahydrate, 6.5 g of cobalt nitrate hexahydrate, 3.9 g of copper nitrate pentahydrate, 0.1 g of chloroplatinic acid (39% Pt), and 5 g of nitric acid were weighed and dissolved in 90 g of deionized water, and 7.7 mL of silica sol (30% alkaline silica sol, silica particle size 10-30 nm) was added dropwise and stirred to mix.

[0077] (2) Mixing and kneading: Weigh 80 g of aluminum hydroxide dry rubber powder, add 5 g of hydroxymethyl cellulose and 5 g of carbon black, add the above-prepared solution to the aluminum hydroxide dry rubber powder containing hydroxymethyl cellulose and carbon black, mix and knead into a uniform paste-like plastic, extrude into 3 mm strips on an extruder, and dry in a drying oven at 110°C for 3 hours, and then calcine in a high-temperature furnace at 550°C for 4 hours to obtain an alumina carrier containing active metal components.

[0078] Comparative Example 4

[0079] A method for preparing a nickel-based supported catalyst comprises the following steps:

[0080] (1) Preparation of pure alumina carrier: Weigh 200 g of aluminum hydroxide dry glue powder, add 10 g of hydroxymethyl cellulose thereto, dilute 4 g of nitric acid in 160 mL of deionized water, add to the aluminum hydroxide dry glue powder containing hydroxymethyl cellulose, knead into a uniform paste-like plastic, extrude into 3 mm strips on an extruder, dry in a drying oven at 110° C. for 3 hours, and then calcine in a high-temperature furnace at 550° C. for 4 hours to obtain a pure alumina carrier.

[0081] (2) Preparation of impregnation solution: Weigh 60 g of nickel nitrate hexahydrate, 6.5 g of cobalt nitrate hexahydrate, 3.9 g of copper nitrate pentahydrate, and 0.1 g of chloroplatinic acid (39% Pt), and dissolve them in 42 g of deionized water.

[0082] (3) Equal volume impregnation: 65 g of the pure alumina carrier prepared in step (1) is impregnated into the impregnation solution prepared in step (2), and the mixture is rotated and impregnated in a water bath at 40°C for 30 min. After adsorption equilibrium is reached, the mixture is heated to 90°C, vacuum-dried, and dried, and then calcined at 400°C for 4 h. The calcined catalyst carrier is then used as a carrier again, and the impregnation solution is prepared again in the same proportion for a second impregnation, adsorption, and calcination. Finally, the calcined oxidized catalyst is heated in a reduction furnace at a hydrogen space velocity of 400 h / min. -1 The reduction was carried out at 420°C for 60 hours. After the reduction was completed, water vapor was introduced to passivate the catalyst surface for 10 hours to obtain a nickel-based supported catalyst.

[0083] Product effect testing

[0084] (1) Physical adsorption characterization tests were performed on the nickel-based supported catalysts or alumina supports containing active metal components prepared in Examples 1-4 and Comparative Examples 1-4, including specific surface area, pore size, and pore volume. Specific characterization data are shown in Table 1.

[0085] Table 1 Physical adsorption characterization data

[0086] Group <![CDATA[Specific surface area (m 2 / g)]]> Pore ​​size (nm) <![CDATA[Pore volume (cm 3 / g)]]> Comparative Example 4 98 6 0.34 Comparative Example 3 225 16 0.56 Comparative Example 1 216 10 0.46 Comparative Example 2 233 21 0.61 Example 1 205 17 0.36 Example 2 197 14 0.30 Example 3 209 15 0.50 Example 4 221 17 0.57

[0087] Analyzing the data in Table 1, it can be seen from Comparative Examples 1 and 4 that the specific surface area of ​​the alumina carrier catalyst containing active metal components prepared by the kneading method in Comparative Example 1 is higher than the specific surface area of ​​the catalyst prepared by the impregnation method in Comparative Example 4. This is because the catalyst prepared by the kneading method is formed by adding a metal salt solution to the raw material and then forming, drying and calcining it once. During the catalyst calcination process, the decomposition and dispersion of the metal salt of the active component is carried out simultaneously with the decomposition of the raw material. The active component is retained in the pores of the carrier, which plays a supporting role in the catalyst structure. Therefore, the kneading method catalyst has a larger specific surface area. The catalyst prepared by the impregnation method is to impregnate the calcined carrier with a metal salt solution. After the carrier is calcined twice, the pores collapse, the specific surface area decreases, and the pore volume decreases. In addition, the active components on the surface and in the pores of the carrier are decomposed into oxides after drying and calcining, and part of the pores of the carrier are blocked by the active components, resulting in the loss of the internal surface area and uneven dispersion of the active components.

[0088] It can be seen from Comparative Examples 1 and 2 that the alumina carrier containing active metal components prepared by kneading with carbon black as a pore expander in Comparative Example 2 improves the pore structure of the catalyst compared to the alumina carrier containing active metal components prepared by kneading without adding a pore expander in Comparative Example 1. The pore expansion principle of physical pore expanders such as carbon black is that during the roasting process, the pore expander wrapped in the aluminum hydroxide dry rubber powder is oxidized into gas and escapes, releasing the space originally occupied, resulting in an increase in the specific surface area, pore volume, and pore size of the carrier. The pore expansion effect of the pore expander molecule is related to the kinetic diameter of the pore expander molecule. After adding carbon black, the pore size within the carrier range increases, which is basically consistent with the particle size of the carbon black particles used. Comparative Example 2 verifies this view.

[0089] From Comparative Examples 2 and 3, it can be seen that the silica sol in Comparative Example 2, which is first added to the aluminum hydroxide dry rubber powder mixed with an extrusion aid and carbon black, has a better pore structure than the alumina carrier containing active metal components prepared by adding the silica sol to the metal mixed solution in Comparative Example 3. This is because the alkaline silica sol may have a neutralization reaction with the metal salt solution, resulting in uneven distribution of the silica sol and the metal salt in the catalyst.

[0090] Examples 1 and 2 The alumina carrier containing active metal components prepared in Comparative Examples 2 and 3 was further impregnated with a metal solution and calcined and reduced to obtain a nickel-based supported catalyst. After further impregnation and calcination and reduction, the specific surface area, pore size and pore volume of the material decreased slightly.

[0091] (2) The metal elements supported on the nickel-based supported catalysts or the alumina supports containing active metal components prepared in Examples 1-4 and Comparative Examples 1-4 were analyzed. The metal element analysis characterization data are shown in Table 2.

[0092] Table 2 Analysis and characterization data of loaded metal elements

[0093] Group Ni(%) Co(%) Cu(%) Pt(%) Comparative Example 4 28.8 3.00 2.60 0.041 Comparative Example 3 15.12 1.43 1.26 0.025 Comparative Example 1 14.74 1.56 1.29 0.028 Comparative Example 2 15.01 1.49 1.32 0.024 Example 1 40.16 4.23 3.91 0.062 Example 2 39.61 4.09 4.03 0.068 Example 3 26.09 2.96 2.73 0.038 Example 4 24.15 3.45 4.18 0.043

[0094] Analyzing the data in Table 2, it can be seen from Comparative Example 4 and Example 1 that the loading of active metals can be greatly increased by coupling the loading and molding processes to prepare a molded catalyst. Comparative Example 4 was prepared by the impregnation method. After two drying and calcination, the pores of the catalyst collapsed, resulting in a decrease in specific surface area and pore volume. Since the equal volume impregnation is based on the active component being impregnated into the porous carrier in the form of a salt solution and infiltrating into the inner surface, due to the limitation of the water absorption rate, the loading of the active component can no longer be increased by multiple impregnations. By comparing Examples 1 and 2 with Comparative Examples 2 and 3, it can be seen that the kneading catalyst improved by the carbon black pore expander loads a part of the metal components by kneading, and at the same time couples the impregnation method to load another part of the metal components, while ensuring the pore structure of the catalyst, it also increases the metal loading.

[0095] (3) Catalyst performance evaluation

[0096] The catalytic performance of the nickel-based supported catalyst or alumina carrier containing active metal components prepared in Examples 1-4 and Comparative Examples 1-4 was evaluated. Polyoxypropylene diamine (D-230) was synthesized using each group of nickel-based supported catalysts or alumina carriers containing active metal components. The specific process is as follows: a fixed bed reactor was filled with a bulk volume of 30 mL of catalyst or alumina carrier, and a reduction treatment was performed at 250°C using a mixture of 10% hydrogen and 90% nitrogen for 12 hours. After the reduction was completed, the temperature was lowered to 200°C, the system pressure was raised to 15MPa and feeding was started. The PPG-230 (polypropylene glycol ether) space velocity was 0.5h -1 The molar ratio of liquid ammonia to PPG-230 was 8:1, and the molar ratio of hydrogen to PPG-230 was 0.8:1. The reactants were distilled to remove excess ammonia and water, and analyzed by gas chromatography. Samples were taken for analysis after 60 hours.

[0097] Among them, the total amine value determination method is: use 0.5 mol / L hydrochloric acid solution to titrate the product, and the total amine value of the product can be calculated by the mass of hydrochloric acid consumed.

[0098] Method for determining secondary / tertiary amine value: After mixing the product with an equal mass of salicylaldehyde and stirring for 2 hours, the product is titrated with 0.5 mol / L hydrochloric acid solution. The sum of the secondary and tertiary amine values ​​of the product can be calculated by the mass of hydrochloric acid consumed.

[0099] Primary amine selectivity = (total amine value - secondary / tertiary amine value) / total amine value x 100%.

[0100] Alcohol conversion rate = total amine value of product / total hydroxyl value of raw materials × 100%.

[0101] The evaluation results of the catalyst activities of each group are shown in Table 3.

[0102] Table 3 Evaluation results of catalyst activity of each group

[0103]

[0104] From the data in Table 3, it can be seen that the overall activity of the catalysts prepared in Examples 1-4 of the present invention is significantly better than that of the catalyst in Comparative Example 4. The nickel-based supported catalyst prepared in the present invention significantly improves the PPG-230 conversion rate and primary amine selectivity, which means that the level of hydrogenolysis by-product generation is low, and the nickel-based supported catalyst prepared in the present invention is an ideal catalyst for polyetheramine synthesis.

[0105] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A method for preparing a supported nickel-based catalyst, characterized in that: The following steps are involved: S1, using the first active metal source, aluminum hydroxide dry rubber powder, extrusion aid, pore expanding agent and silica sol as raw materials, and preparing an alumina carrier containing active metal components by kneading and molding; S2, using a second active metal source to prepare an impregnation solution, then impregnating the alumina support prepared in step (1), and then calcining to obtain a supported nickel-based catalyst; In step S1 and step S2, the first active metal source and the second active metal source both include a nickel source, a platinum source, a copper source and a cobalt source.

2. The preparation method according to claim 1, characterized in that: The preparation process of step S1 includes any one of the following two methods: (1) dissolving a first active metal source in water to prepare a kneading solution; adding an extrusion aid, a pore-enlarging agent and a silica sol to aluminum hydroxide dry rubber powder, mixing them evenly, adding the kneading solution to knead, and then molding, drying and calcining to prepare an alumina carrier containing active metal components; (2) dissolving the first active metal source in water, adding silica sol, and preparing a kneading solution; taking aluminum hydroxide dry rubber powder, adding an extrusion aid and a pore expander, mixing evenly, adding the kneading solution to knead, and then forming, drying, and calcining to prepare an alumina carrier containing active metal components.

3. The preparation method according to claim 1 or 2, characterized in that: The silica sol includes alkaline silica sol or acidic silica sol.

4. The preparation method according to claim 1 or 2, characterized in that: The extrusion aid includes at least one of sesbania powder, starch, cellulose and carbon powder.

5. The preparation method according to claim 1 or 2, characterized in that: The pore expanding agent is carbon black.

6. The preparation method according to claim 2, characterized in that: In the method (1) or the method (2), a peptizing agent is also added when preparing the kneading solution; the peptizing agent is selected from at least one of an inorganic acid, an organic acid, and a strongly acidic anionic aluminum salt.

7. The preparation method according to claim 2, characterized in that: In method (1) or method (2), the calcination process is: calcination at 400-500° C. for 2-8 hours.

8. The preparation method according to claim 2, characterized in that: In step S2, the impregnation process is: placing the alumina carrier in the impregnation solution, and impregnating it for 20-60 minutes at 35-45° C. and in a rotating state.

9. The preparation method according to claim 2, characterized in that: In step S2, the calcination process is: calcination at 400-500°C for 3-8 hours.

10. A method for preparing a polyetheramine, characterized in that: The polyetheramine is synthesized using a supported nickel-based catalyst prepared by the preparation method described in any one of claims 1 to 9.

Citation Information

Patent Citations

  • Demetallizing catalyst and preparation method thereof

    CN104549332A

  • Method for preparing hydrodemetallization catalyst

    CN105521793A

  • Preparation method of flue gas reduction desulfurization catalyst

    CN107774278A

  • Regeneration method of amination catalyst of polyetheramine used for polyether polyol hydro-amination

    CN107961797A

  • Hydrogenating denitrification catalyst of heavy oil

    CN1086534A

Cited By

  • Preparation method for supported nickel-based catalyst, and polyetheramine prepared from catalyst

    WO2026103090A1